Motivational factors and academic performance in the hybrid modality: Motivación para un aprendizaje significativo - Ledesma Silva, Yolanda Esperanza; Cobos Reina, Ángel Rodrigo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
As an objective, the relationship between motivational factors and academic performance was determined. The research was quantitative with a cross-sectional correlational design. The sample was 315 students from two Faculties of the Central University of Ecuador. A questionnaire of 27 questions with a Likert scale was applied. For statistical analyses, SPSS V25 software was used. The main result gave a Pearson correlation of 0.827, being strong positive between the two variables. In addition, the relationship with the different dimensions of each variable was analyzed. In conclusion, motivation improves the academic performance of students.